Clinical features of neuromyelitis optica in children: US Network of Pediatric MS Centers report. (19th January 2016) - Chitnis, Tanuja; Ness, Jayne; Krupp, Lauren; Waubant, Emmanuelle; Hunt, Tyler; Olsen, Cody S.; Rodriguez, Moses; Lotze, Tim; Gorman, Mark; Benson, Leslie; Belman, Anita; Weinstock-Guttman, Bianca; et al.
Abstract : Objective: To compare clinical features of pediatric neuromyelitis optica (NMO) to other pediatric demyelinating diseases. Methods: Review of a prospective multicenter database on children with demyelinating diseases. Case summaries documenting clinical and laboratory features were reviewed by an adjudication panel. Diagnoses were assigned in the following categories: multiple sclerosis (MS), acute disseminated encephalomyelitis, NMO, and recurrent demyelinating disease not otherwise specified. Results: Thirty-eight cases of NMO were identified by review panel, 97% of which met the revised International Panel on NMO Diagnosis NMO-SD 2014 criteria, but only 49% met 2006 Wingerchuk criteria. Serum or CSF NMO immunoglobulin G (IgG) was positive in 65% of NMO cases that were tested; however, some patients became seropositive more than 3 years after onset despite serial testing. No patient had positive CSF NMO IgG and negative serum NMO IgG in contemporaneous samples. Other than race ( p = 0.02) and borderline findings for sex ( p = 0.07), NMO IgG seropositive patients did not differ in demographic, clinical, or laboratory features from seronegatives. Visual, motor, and constitutional symptoms (including vomiting, fever, and seizures) were the most common presenting features of NMO. Initiation of disease-modifying treatment was delayed in NMO vs MS. Two years after onset, patients with NMO had higher attack rates, greater disability accrual measured by overall Expanded Disability Status Scale score, and visual scores than did patients with MS. Conclusion: The new criteria for NMO spectrum disorders apply well to the pediatric setting, and given significant delay in treatment of NMO compared to pediatric MS and worse short-term outcomes, it is imperative to apply these to improve access to treatment.